(untitled) (Historia, 2021)
History and journalism : a symbiotic model for South African schools of journalism The decline in general knowledge and, more specifically, knowledge of history, among students has become a serious problem to lecturers in journalism courses worldwide. But it also reflects detrimentally on the media employing these students, as the media are becoming more and more the target of criticism for superficiality and lack of contextual references in news reports. This article is an empirical analysis of the knowledge of history among a group of 130 applicants for the B.Honours degree at the University of Stellenbosch. The Stellenbosch journalism programme is the only specialised postgraduate course of its kind in South Africa. One would expect students coming into the course, to have a broader general knowledge than those studying journalism at undergraduate level. The necessity of introducing a level of basic history to journalism students in South African tertiary institutions is studied in the light of the research undertaken into cultural literacy by E.D. Hirsch and others in the U.S.A. A comparison is also made between the levels of historical knowledge of students with a background of history at tertiary level, and those with no history background. Die gebrekkige algemene kennis, en meer spesifiek die swak kennis van geskiedenis van studente, begin wêreldwyd ernstige probleme skep vir dosente in joernalistiek. Verder reflekteer dit ook negatief op die media wat hierdie studente in diens neem en toenemend onder kritiek moet deurloop weens die oppervlakkigheid van en die gebrek aan kontekstuele verwysing in nuusberigte. Hierdie artikel is 'n empiriese ontleding van die kennis van geskiedenis onder 'n groep van 130 aansoekers vir toelating tot die B.Honneursgraad in joernalistiek aan die Universiteit van Stellenbosch. Die Stellenbosch joernalistiekprogram is die enigste gespesialiseerde nagraadse joernalistiekprogram in Suid-Afrika. 'n Mens sou dus 'n beter algemene kennis van hierdie potensiële studente verwag. Die artikel ondersoek die noodsaaklikheid van 'n studie van geskiedenis vir joernalistiekstudente in die lig van navorsing oor kulturele geletterdheid deur E.D. Hirsch en andere in die V.S.A. 'n Vergelyking word ook getref tussen studente met voorgraadse opleiding in geskiedenis en die daarsonder.